Temperature Estimation of Geothermal Systems and Subsurface Model Based on Geochemical of Lake Ranau - Mochammad Malik Ibrahim; Agung Harijoko; Wiwit Suryanto (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
The geothermal potential of the Lake Ranau area comes from the remnants of magmatic activity from Mount Seminung. Geothermal manifestations in this area are in the form of hot springs that are thought to emerge through geological structures. This research aims to determine the approximate temperature of the geothermal system and subsurface model based on the analysis of chemical geothermometer method. The chemical geothermometer method can be used to indirectly predict the temperature of the subsurface geothermal system. Geothermal fluid manifestations in Kota Batu Village were chemically sampled by collecting three samples (LP 1, LP 2, and LP 3) and in Lombok Village by collecting three samples (LP 4, LP 5, and LP 6). Chemical geothermometers used in the research are silica, Na/K, K/Mg and Na-K-Ca geothermometers. The results of chemical geothermometer calculations on 6 samples of geothermal fluid manifestation locations, the estimated temperature of the subsurface geothermal system in the research area ranges from 177.0 - 285.6 0C and is included in the geothermal system with medium to high enthalpy. The subsurface model based on the calculation results of various chemical geothermometers about geothermal system components such as cap rock, reservoir rock, heat source, geological structure, thermal fluid and surface manifestations.